2020
DOI: 10.1308/rcsann.2020.0135
|View full text |Cite
|
Sign up to set email alerts
|

Should the rectal defect be sutured following TEMS/TAMIS carried out for neoplastic rectal lesions? A meta-analysis

Abstract: Introduction Management of the rectal defect following transanal endoscopic microsurgery (TEMS) or minimally invasive surgery (TAMIS) carried out for excision of neoplasm in the lower rectum is controversial. We aimed to extract evidence by carrying out a meta-analysis to compare the peri- and postoperative outcomes following rectal neoplasm excision carried out by TEMS and/or TAMIS, whereby the defect is either sutured or left open. Methods A literature search of Ovid MEDLINE and EMBASE was performed. Full-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(36 reference statements)
1
8
0
1
Order By: Relevance
“…Reoperation was performed due to bleeding, rectal perforation, residual cancer, pelvic abscess, and nonhealing wound. Khan et al [ 46 ] reported closure of the rectal defect, which accounts for a major part of the operating time. It has also been reported that defect closure reduces the risk of re-bleeding, but has no effect on postoperative infection and hospital stay[ 46 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Reoperation was performed due to bleeding, rectal perforation, residual cancer, pelvic abscess, and nonhealing wound. Khan et al [ 46 ] reported closure of the rectal defect, which accounts for a major part of the operating time. It has also been reported that defect closure reduces the risk of re-bleeding, but has no effect on postoperative infection and hospital stay[ 46 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Closing the defect resulted in significantly decreased rate of post-operative bleeding as compared to leaving the defect open. However, there was no statistical difference in postoperative infection, operative time and length of hospital stay between the two groups (14). In our series, we routinely closed all the defects.…”
Section: Discussionmentioning
confidence: 64%
“…For lesions with any suspicion of malignancy, a full thickness resection should be performed with transmural dissection up to the mesorectal fat. Following lesion excision, closure of the rectal wall defect is warranted for cases where there has been inadvertent intra-peritoneal entry or where there has been a planned dissection above the peritoneal reflection for proximal lesions[ 39 ]. For resections below the peritoneal reflection there is a lack of consensus on whether the defect should be closed and it is largely dependent on surgeon preference.…”
Section: Local Excision Techniquesmentioning
confidence: 99%
“…A meta-analysis conducted by Khan et al [ 39 ] in 2020 assessed outcomes of TEM/TAMIS in cases where the defect was sutured ( n = 283) in comparison to cases where it was left open ( n = 272). Authors found no statistically significant differences in rates of post-operative infection, length of hospital stay or duration of procedure; although there was a trend towards longer operations in the defect closure group.…”
Section: Local Excision Techniquesmentioning
confidence: 99%